Ода «Вольность» Радищева. Распад империи, апокалипсис и поэтический надрыв - Zehnder, Christian (Wiener Slawistischer Almanach, 2025)
This essay proposes to return to Viktor Zhivov‘s (1945–2013) thesis about the apocalyptic nature of Radishchev’s ode “Liberty” (Vol′nost′, 1783) by asking three questions: First, how does this apocalypticism correlate with the notorious “revolutionary” and deeply populist character of the poem; second, how should both of these features (apocalypse and revolution) be linked with the imagined disintegration of the empire in Radishchev’s ode; and third, to what extent does the apocalyptic politics and centrifugal dynamics of “Liberty” correspond to any artistic innovation? Zhivov considers the first question in his article, while he brackets the second and the third is beyond his scope. Entering a dialog with Zhivov‘s thesis, this essay looks at the complex of problems (populism, empire, apocalypse) in close connection with the precariousness or instability of Radishchev’s very poetic language.